2017
DOI: 10.1111/head.13194
|View full text |Cite
|
Sign up to set email alerts
|

Headache Education Active‐Waiting Directive: A Program to Enhance Well‐Being During Long Referral Wait Times

Abstract: The HEAD program, created to help manage lengthy appointment wait times, was associated with lowering migraine-associated disability, decreasing ED visits, reducing medication and narcotic use and overuse. Education empowers patients to take an active role in their care, especially in regards to improving treatment timing and modifiable lifestyle behaviors. This education program can potentially play a role in early intervention for headache patients especially with chronic migraine and medication overuse head… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 35 publications
0
8
0
3
Order By: Relevance
“…Wait times for appointments to see an outpatient provider may also limit health care access, and in general, the more specialized the care, the longer the wait. Research has shown that wait times for specialty care can range from months and in certain cases to more than a year (48,54). Long wait times to receive both acute care in emergent settings as well as chronic care in outpatient settings are a concerning deterrent, preventing patients from seeking health care in the…”
Section: Timely Provision Of Carementioning
confidence: 99%
“…Wait times for appointments to see an outpatient provider may also limit health care access, and in general, the more specialized the care, the longer the wait. Research has shown that wait times for specialty care can range from months and in certain cases to more than a year (48,54). Long wait times to receive both acute care in emergent settings as well as chronic care in outpatient settings are a concerning deterrent, preventing patients from seeking health care in the…”
Section: Timely Provision Of Carementioning
confidence: 99%
“…В связи с этим образование пациентов наряду с другими нефармакологическими подходами становится одним из стратегических направлений в ведении пациентов с частыми формами цефалгий [15,28,29]. Эффективность образовательных программ неоднократно показана в различных исследованиях [24,[30][31][32][33][34]. Одним из важных направлений является выявление пациентов из группы риска хронификации ГБ.…”
Section: Discussionunclassified
“…В норвежском проспективном когортном исследовании 109 человек из общей популяции с хронической первичной ГБ и чрезмерным употреблением лекарств краткое информирование пациентов сопровождалось значительным сокращением частоты приема лекарств и частоты ГБ [29]. Образовательные программы стали неотъемлемой частью ведения пациентов с ЛИГБ как мера, повышающая эффективность их лечения в целом [31,33,34].…”
Section: Discussionunclassified
“…Physicians may not have the time or communication skills to effectively counsel patients 3 . Education sessions have been found to be effective to improve outcomes and limit visit to the emergency department, but organizing and funding such sessions is not always possible 4 . The amount of misleading information available online is significant.…”
Section: A Need For Therapeutic Education Toolsmentioning
confidence: 99%